Revisorn och den institutionaliserade misstron: professionaliseringen av svensk bolagsrevision (Sociologisk Forskning, 2007)
The auditor and the insitutionalization of distrust: the professionalization of external auditing in SwedenThis paper addresses professionalization with a focus on trust, rather than on issues of power and competition. It contains a conceptual analysis of trust/confidence, as well as a case study of the professionalization of external auditing in Sweden. The conceptual analysis discusses the “time-binding” aspect of trust/confidence, and the significance of social control mechanisms related to “persons”, “roles”, “values” and “programs” for creating and sustaining trust/confidence. The case study focuses on the role of trust/confidence for the organization and professionalization of external auditing in Sweden, and in particular on the ways in which trust in auditors and auditing have been stabilized. The latter issue is dealt with through a discussion attempting to capture a historic displacement in three dimensions: from reliance on the auditor’spersonal reliability, to trust in the professional role; from trust in the individual discretion of certain persons to trust in the regulation of auditing as a standardized program; and finally, from trust in the values represented by individual auditors to trust in the institutionalized professional values.
Keywords: trust; confidence; social control; professions; auditors; auditing